2023
DOI: 10.3390/agronomy13092394
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on Grassland Eco-Assets and Eco-Products and Its Implications for the Enhancement of Ecosystem Service Function of Karst Desertification Control

Kangning Xiong,
Cheng He,
Yongkuan Chi

Abstract: Grasslands in karst ecological fragile areas can effectively mitigate climate change, conserve biodiversity, maintain human well-being, and play a significant role in improving the health of regional ecosystems and farmers’ livelihoods. Thus, the study of grassland ecological assets and ecological products comprehensively examines their effects on grassland ecosystem services based on the traditional paradigm. This procedure is crucial from a strategic perspective for rebuilding damaged grassland ecosystems in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 102 publications
1
4
0
Order By: Relevance
“…The high-value areas were primarily distributed in mountain forests and lake wetlands, with high regional vegetation coverage, including nature reserves and parks with less surface disturbance. This was similar to the results of other studies in Guangxi [31,34,40]. The results also indicated that there was a decreasing trend of biodiversity in Guilin from 2000 to 2020, and the areas of biodiversity reduction were primarily concentrated around towns (Figure 5d).…”
Section: Analysis Of Biodiversity Changesupporting
confidence: 90%
See 1 more Smart Citation
“…The high-value areas were primarily distributed in mountain forests and lake wetlands, with high regional vegetation coverage, including nature reserves and parks with less surface disturbance. This was similar to the results of other studies in Guangxi [31,34,40]. The results also indicated that there was a decreasing trend of biodiversity in Guilin from 2000 to 2020, and the areas of biodiversity reduction were primarily concentrated around towns (Figure 5d).…”
Section: Analysis Of Biodiversity Changesupporting
confidence: 90%
“…Therefore, this study took CL, AL, and transportation land as threat factors. This study determined the sensitivity assignment of different habitat types (Table 1), the weight of threat factors, and the maximum impact distance of threat sources (Table 2) concerning the literature review and InVEST model manual and the specific conditions of the study area [40][41][42]. The greater the complexity of ecosystems, the better the state of the landscape structure, and the more balanced the categories within a given area, the greater the degree of landscape diversity [43].…”
Section: The Hq Assessment Based On the Invest Modelmentioning
confidence: 99%
“…(1) The management and utilization of traditional grasslands [16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…Abakumov et al [27] studied the influence of land use type (pasture, vegetable garden, hayfield, or secondary afforestation) on key agrochemical parameters and the parameters of soil microbial biodiversity and found that the key factor regulating soil microbiome composition shifts was the duration and degree of the irreversibility of an agrogenic impact. Xiong et al [28] analyzed 143 pertinent works on grassland ecological assets and ecological products and proposed insights into the enhancement of karst grassland ecosystem service functions based on three perspectives: a fragile environment, trade-off synergy, and service management. This study provides valuable insights for the development of regional ecological livestock and the scientific promotion of integrated desertification control.…”
Section: The Management and Utilization Of Traditional Grasslandsmentioning
confidence: 99%
“…Grassland in the KDC area is a special ecosystem formed by using ecological engineering measures (e.g., returning farmland to grassland, grassland establishment, etc.) to control karst desertification (a concentrated manifestation of karst land degradation; Xiong et al, 2023). In contrast to the grassland in non-karst area (e.g., the tropical and subtropical savannas and temperate steppes, and arctic-alpine grasslands, etc.…”
Section: Introductionmentioning
confidence: 99%